Study of the Metatranscriptome of Eight Social and Solitary Wild Bee Species Reveals Novel Viruses and Bee Parasites - Schoonvaere, Karel; Smagghe, Guy; Francis, Frédéric; de Graaf, Dirk C. (Frontiers in Microbiology, 2018)
Bees are associated with a remarkable diversity of microorganisms, including unicellular parasites, bacteria, fungi and viruses. The application of next-generation sequencing approaches enables the identification of this rich species composition as well as the discovery of previously unknown associations. Using high-throughput polyadenylated RNA sequencing, we investigated the metatranscriptome of eight wild bee species (Andrena cineraria, Andrena fulva, Andrena haemorrhoa, Bombus terrestris, Bombus cryptarum, Bombus pascuorum, Osmia bicornis and Osmia cornuta) sampled from four different localities in Belgium. Across the RNA sequencing libraries, 88 to 99 % of the taxonomically informative reads were of the host transcriptome. Four viruses with homology to insect pathogens were found including two RNA viruses (belonging to the families Iflaviridae and Tymoviridae, that harbour already viruses of honey bees), a double stranded DNA virus (family Nudiviridae) and a single stranded DNA virus (family Parvoviridae). In addition, we found genomic sequences of 11 unclassified arthropod viruses (related to negeviruses, sobemoviruses, totiviruses, rhabdoviruses and mononegaviruses), seven plant pathogenic viruses and one fungal virus. Interestingly, nege-like viruses appear to be widespread, host-specific and capable of attaining high copy numbers inside bees. Next to viruses, three novel parasite associations were discovered in wild bees, including Crithidia pragensis and a tubulinosematid and a neogregarine parasite. Yeasts of the genus Metschnikowia were identified in solitary bees. This study gives a glimpse of the microorganisms and viruses associated with social and solitary wild bees and demonstrates that their diversity exceeds by far the subset of species first discovered in honey bees.